Control of Rhizome Rot Disease of Ginger (Zingiber officinale Rose) by Chemicals, Soil Amendments and Soil Antagonis (The Agriculturists, 2010)
Two field experiments were conducted at domar and sadar upzilla of Nilphamari district to find out an effective control measure against rhizome rot (Pythium aphanidermatam) disease of ginger (Zingiber officinale Rose). Each experiment consisted of nine treatments, where three fungicides (Ridomil, Metataf and Secure), three organic amendments (poultry refuse, mustard oilcake and saw dust burning) and two bio control agents (Trichoderma harzianum and T. viride) were tested. Fungicides were used as seed treatment and soil drenching and organic materials and bio control agents were used as pre plant soil amendments. All the treatments significantly decreased the incidence and severity of the diseases and increased germination, tiller number and rhizome yield. The most effective treatment was seed treatment (0.2%) and soil drenching (0.2%) with Ridomil gold. Seed treatment and soil drenching with Secure (0.1%) and soil amendment with poultry refuse (10 t/ha) were also found to be effective to control the diseases and to increase rhizome yield.